Memory clinic survey in New Zealand: a second look. (October 2019) - Stone, Constance; Copeland, Bronwyn; Collier, Cheryl; Cheung, Gary
Objective: To investigate the changes in publicly funded memory clinics in New Zealand's since the last survey in 2008. Method: We conducted an online survey of the 20 District Health Boards (DHBs) and gathered information on the recently discontinued or established memory clinics. Results: We found dedicated memory clinics in the seven DHBs that have the largest older persons populations in New Zealand. Those DHBs that had discontinued their memory clinics did so because they opted for a more integrated approach using their primary care based dementia care pathway. Increased waiting times, low staffing ratios, variance in cognitive screening tests and patient demographics were reported. Conclusions: There is significant variability in the structure of memory clinics in New Zealand. These clinics could benefit from collaboration and bench-marking of their services.